Algebraic Thinking Ability of class 7 SMP on Material Algebraic Form - Hasibuan, FH; Dasari, D (International Conference on Elementary Education, 2020)
Algebraic thinking ability is one of the mathematical thinking abilities that students must have because algebraic skills are needed in other materials, such as exponents, logarithms, trigonometry and so on. The purpose of this study was to determine the algebraic thinking skills of 7th grade middle school students in solving algebra problems. The research method used is a qualitative descriptive approach. The research instrument used was an algebraic thinking ability and interview test. The results of the analysis of this study indicate that generational, transformational, and global meta-level skills have been seen in some 7th grade students. Students who are in high-level groups have high generational, transformational, and meta-global abilities, students in moderate groups have high generational capability, moderate transformational, and low to moderate global meta-level. Whereas the ability of students in low groups has low to moderate generational abilities, moderate transformational and low global meta-levels